Role of S-100 stain for demonstration of different patterns of nerve changes in spectrum of leprosy – A prospective study - Deepti Gangwar; Javed Iqbal; Pooja Jaiswal; Sara Siddiqui; Rumpa Das; Shalini Suman (Asian Journal of Medical Sciences, 2022)
Background: A confirmatory diagnosis of tuberculoid (TL) and borderline TL (BTL) leprosy is dependent on the demonstration of nerve involvement within granuloma or acid-fast bacilli. It is very difficult to identify nerve elements in hematoxylin and eosin (H&E) stains. S-100 stain in this study is used to highlight nerve in TL leprosy so as to reach a definitive diagnosis of TL leprosy.